2023
DOI: 10.52628/89.1.11029
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measurement of median nerve and wrist skin thickness in patients with carpal tunnel syndrome: relationship with clinical, electrophysiologic and functionality

Abstract: The study aimed to investigate the relationship between the proximal and distal cross-sectional area (CSA) of the median nerve and wrist skin thickness measured by ultrasound in patients with carpal tunnel syndrome (CTS), demographics, disease characteristics, electrophysiological measurements, symptom severity, functionality, and symptom severity. 98 patients with electrophysiological diagnoses of CTS in the dominant hand were included in the study. Proximal and distal CSAs of the median nerve and wrist skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Ultrasonography (US) has been shown to be a reliable tool for detecting the morphology of the bifid MN, which is generally not an infrequent variation, particularly in hands with CTS [30][31][32]. It is also important in the diagnosis of CTS, based on the enlargement of the MN with an area greater than 9 mm² or 10 mm² at the level of the pisiform bone [33][34][35][36]. Monagle et al, [37] demonstrated with magnetic resonance imaging that the MN in CTS was enlarged both proximally and within the carpal tunnel.…”
Section: Lanz [9]mentioning
confidence: 99%
“…Ultrasonography (US) has been shown to be a reliable tool for detecting the morphology of the bifid MN, which is generally not an infrequent variation, particularly in hands with CTS [30][31][32]. It is also important in the diagnosis of CTS, based on the enlargement of the MN with an area greater than 9 mm² or 10 mm² at the level of the pisiform bone [33][34][35][36]. Monagle et al, [37] demonstrated with magnetic resonance imaging that the MN in CTS was enlarged both proximally and within the carpal tunnel.…”
Section: Lanz [9]mentioning
confidence: 99%